2018
DOI: 10.1093/jisesa/iey056
|View full text |Cite
|
Sign up to set email alerts
|

Gene Cloning, Prokaryotic Expression, and Biochemical Characterization of a Soluble Trehalase in Helicoverpa armigera Hübner (Lepidoptera: Noctuidae)

Abstract: Trehalase is an indispensable component of insect hemolymph that plays important role in energy metabolism and stress resistance. In this study, we cloned and expressed the gene encoding soluble trehalase (HaTreh-1) of Helicoverpa armigera (cotton bollworm) and characterized the enzyme. HaTreh-1 had a full-length open reading frame encoding a protein of 571 amino acids. Sequence comparison indicated that HaTreh-1 was similar to some known insect trehalases. Two essential active sites (D321 and E519) and three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…k cat is evaluated at 143 s −1 , and k cat /K m is 2 mM −1 .s −1 . This is in agreement with the K m values ranging from 0.5 to 73 mM that have been reported from other insects trehalases, such as Apis mellifera (0.52 mM) [52], Artemia Embryos (8.4 mM) [19], Bombyx mori (0.46 mM) [20], Aphis citricola (6.4 mM from alate -7.2 mM from apterous) [26], Chaetomium aureum (0.7 mM) [53] and Helicoverpa armigera (72.8 mM) [8].…”
Section: Catalytic and Kinetics Properties Of The Enzymementioning
confidence: 77%
See 2 more Smart Citations
“…k cat is evaluated at 143 s −1 , and k cat /K m is 2 mM −1 .s −1 . This is in agreement with the K m values ranging from 0.5 to 73 mM that have been reported from other insects trehalases, such as Apis mellifera (0.52 mM) [52], Artemia Embryos (8.4 mM) [19], Bombyx mori (0.46 mM) [20], Aphis citricola (6.4 mM from alate -7.2 mM from apterous) [26], Chaetomium aureum (0.7 mM) [53] and Helicoverpa armigera (72.8 mM) [8].…”
Section: Catalytic and Kinetics Properties Of The Enzymementioning
confidence: 77%
“…The hydrolysis of trehalose into two glucose molecules takes place under the enzymatic control of trehalase (Treh) (EC 3.2.1.28). This enzyme was first discovered in Aspergillus niger in 1893 [5], and detected in various organisms [1][2][3][6][7][8]. According to the latest classification system of glycoside hydrolases based on their amino acid sequence similarity, Treh is an inverting glycosidase [9] belonging to either of the families 15, 65, and 37.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trehalose and trehalase are found in several insects, such as Helicoverpa armigera [27], Spodoptera frugiperda [28], S. litura [29], Anisakis simplex [30], and the European honeybee [19]. Trehalose has important physiological effects on insect growth and development, energy for flight, chitin biosynthesis regulation [31], and restoration of abiotic stress.…”
Section: Animals and Plantsmentioning
confidence: 99%
“…Recent studies have indicated that only Tre-1 and Tre-2 are found in the majority of insects, such as Apolygus lucorum (Tan et al, 2014), Helicoverpa armigera (Ai et al, 2018), Spodoptera exigua (Tang et al, 2008), Omphisa fuscidentalis (Tatun et al, 2008), Drosophila melanogaster (Shukla et al, 2016), Cnaphalocrocis medinalis (Tian et al, 2016), and Bemisia tabaci (Wang et al, 2014). Multiple Tre-1 have been cloned in insects, including Harmonia axyridis (Tang et al, 2014;, Locusta migratoria , Nilaparvata lugens (Zhao et al, 2016), Tribolium castaneum (Tang et al, 2016), and Leptinotarsa decemlineata .…”
Section: Introductionmentioning
confidence: 99%